Self-reference and (dis) equilibrium of psychomental complex: ethnic policies of 'social (dis) harmony' in Northeast China and 'national (dis) unity' in the Russian Far East. Issue 1 (2nd January 2016) - Oleg, Pakhomov
Abstract : This work is an attempt to describe the reproduction of ethnic/national boundaries as a closed self-referential cognitive process that reproduces itself from itself. It describes some aspects of how this complex interrelation between cognitive structures and the formation of ethnic/national groups functions on the example of ethnic policies of 'social harmony' on the Northeast China and 'national unity' in the Russian Far East. The article shows how ethnic policies in both countries demonstrate the inability to provide either harmony or unity. However, these disappointed expectations return into national discourse as political ideologies that help preserve the government's legitimacy, legitimacy of the idea of nation/ethnicity and motivate the society to continue the nation-building process.